Islamizing and internationalizing higher education and satisfaction: a case study from international muslim student perspective - Ahmed, Faruk; Huque, Ahasanul; Omar, Azura; Mohd. Israil, Khaliq Ahmad (Malaysian Institute of Management (MIM), 2017)
Purpose of the study is to explore satisfaction of Islamization and internationalization of higher education from the perspective of international Muslim students. Hope theory (Snyder, 2002) and tow-factors of emotion theory (Schachter & Singer, 1962) are thought appropriate for guiding the research on mind state of international Muslim students’ expectation and satisfaction towards Islamization and internationalization of higher education served by International Islamic University Malaysia. According to the theory and satisfying concept, research questionnaire was designed with case study. Among more than 105 countries this study included five countries for interview with the students of this university. Bangladesh, Nigeria, Indonesia, Yemen, and Syria were the names of countries which were selected to take in-depth interview with a view to exploring their inner psychological and emotional states that are context-specific and context-free from this perspective. This attempt has been made to expose a relationship between international standard quality of Islamized higher education and satisfaction from international Muslim student’s point of view, which is a rare attempt in tertiary education field. Result of the study was obtained as a positive link between Islamisation and internationalization and satisfaction of higher education. This result implied a value that would be useful for making decisions by administration of a higher education institution in improving quality for attracting foreign Muslim students.